Expressive Speech Act on Pamphlet Demonstration Rejecting the Omnibus Law Bill - Bayu Suta Wardianto; Abdul Wachid Bambang Suharto; Kim Young Soo (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
Human expression in venting its emotions through language becomes a very interesting thing to discuss and research. In this study, the expression of language contained in the protest pamphlet on the rejection of the Omnibus Law Bill will be classified and analyzed based on its nature and function in expressive speech. In the research method used is qualitative dextriptif. The data that will be examined in the form of writings contained in pamphlets on the omnibus law rejection demonstrations that took place in the center and the region. The techniques used in the processing and analysis of data in this study are with the stages of data collection, data reduction, and data presentation. The results of the study found a form of expressive speech in the pamphlet demonstration of omnibus law rejection. The expressive action on the demonstration pamphlet Reject Omnibus Law based on its nature is divided into two, namely constructive and destructive speech. Both traits are based on speech that builds or decreases the public perception of the existing speech. Expressive speech also has the function of giving greetings, apologizing, praising, insulting, blaming, mocking, and condolences. Abstracts are written in a single paragraph consisting of 200 words, without libraries/citations.